The roles of teaching methods,teachers’ self-efficacy, ICT resources and intrinsic motivation in the teaching of english culture in EFL classrooms in Algeria - Ryma, Guechi (2022)
Foreign language teaching needs to be instructed on the cultural background of the target language. Despite this, it seems that the inclusion of culture is still overlooked in many language classrooms. Moreover, empirical research on the relationship between teaching methods, teachers’ self-efficacy, ICT resources and the teaching of English culture is scarce in the EFL context. Furthermore, there is limited research on the relationship between teaching methods, teachers' self-efficacy, ICT resources and the teaching of culture using teacher intrinsic motivation as a moderator. This study sought to examine the situation of cultural teaching in the high schools of the eastern part of Algeria. More specifically, it attempted to find out whether culture is given much importance in language classrooms and whether Algerian EFL teachers are cognizant of the significance of culture in their teaching of English. Moreover, this study proposed that teachers’ intrinsic motivation might moderate the relationship between teaching methods, teachers’ self-efficacy, ICT resources and the teaching of English culture. This study employed the mixed-method explanatory sequential research design in which quantitative data using questionnaires was collected by employing the simple random sampling of 379 Algerian EFL teachers. Besides, qualitative data was gathered through semi-structured interviews with ten Algerian EFL teachers using homogeneous purposeful sampling. The findings indicated that the effect of teaching methods, teachers’ self-efficacy and ICT resources on the teaching of culture was significant. Furthermore, teachers’ intrinsic motivation moderated the relationship between all the constructs and the teaching of culture. The qualitative findings revealed that several factors were responsible for the influence of teaching methods, teachers’ self-efficacy and ICT resources in the teaching of English culture. The findings offer several implications for EFL teachers and policy-makers in terms of increasing their self-efficacy and improving their teaching approaches as well as providing convenient resources for enhancing culture teaching.